Development and optimization of large-scale approaches to identify iron-related genes in Aspergillus fumigatus - Baldin, Clara; Binder, Ulrike; Scheler, Jakob; Werner, Ernst R.; Gsaller, Fabio; Bromley, Michael J.; Haas, Hubertus (Frontiers in Microbiology, 2025)
Recent advancements in genetic engineering have enabled the creation of extensive mutant libraries across various species, driving the need for efficient screening methods to identify mutants of interest. In this study, we developed and optimized two rapid and straightforward screening techniques to identify genes involved in iron metabolism. Iron is an essential element for almost all organisms, and in pathogens, the ability to acquire iron from the environment and mitigate the toxic effects of intracellular iron often plays a crucial role in virulence. The first screening method exploits the autofluorescence property of porphyrins, while the second one is an optimization of growth assay on solid-agar suitable for large scale analyses. To validate these methods, we applied them to a recently published protein kinase deletion mutant library in Aspergillus fumigatus, a fungal pathogen that causes severe diseases in immunocompromised individuals. Our iron-specific screening approaches successfully identified strains with altered iron metabolism, including both previously known and novel mutants, generating a small set of genes that can serve as new targets for antifungal therapies. These methodologies provide the first large-scale tool for exploring iron metabolism-related genes and can be adapted for other organisms with available mutant libraries.